Impact of chlorpyrifos on the ovary of the freshwater fish, channa punctatus (Funded Work) - ABHA MISHRA,; PARMESHWAR SINGH, (International Journal of Pharma and Bio Sciences, 2018)
The present study focuses on the toxic effects of Chlorpyriphos on the ovary of Channa punctatusby using histological and histochemical techniques. In order to analyze, two concentrations of Hilban (20% EC CPF) {0.538 µl.L-1, 1.79 µl.L-1 (1/10th, 1/3rd of 24h LC50 for 7, 3 days respectively)} were used during the pre-spawning phase along with the control. The anatomical study showed visible changes due to CPF toxicity in both long and short treatment groups when compared to control group. The study also indicated the disruption of follicles, vacuolization of oocytes, damage in germinal epithelium, atresia of oocyte and inter-follicular oedema. The Mallory stain revealed the separation of ovarian follicles due to loss of interfollicular connective tissue and the Necrosis and fibrosis of connective tissue were also observed. The histochemical analysis of control fish demonstrated that the calcium and carbohydrate-positive reactions decreased with the Chlorpyrifos-treated groups except in iron staining. The iron pigments were more visible in the treated groups due to the breakdown of Heme. The results indicate that Chlorpyrifos affects the critical biochemical contents of the ovary. The toxicological effects were more apparent in groups of extended duration than in the other and suggested the accumulative nature of CPF in addition to its internal biochemical alterations.